1984
DOI: 10.1111/j.1365-2125.1984.tb02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective binding of propranolol enantiomers to human alpha 1‐ acid glycoprotein and human plasma.

Abstract: The binding of propranolol enantiomers to human albumin (ALB), al-acid glycoprotein (aI-AGP) and plasma was studied. (-) propranolol is more bound than (+) propranolol to a1-AGP (P < 0.001) and to plasma (P < 0.05). In solutions containing ALB at a constant concentration (580 ,umol/l) and a1-AGP at increasing concentrations, the binding of both isomers increases but the stereo selectivity is evident throughout the a1-AGP concentration range examined (25-100 ,umol/l).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 12 publications
4
21
0
Order By: Relevance
“…Although the differences were small, the data nonetheless are consistent with previous reports that have demonstrated the stereoselective binding of (-)-propranolol in young, healthy volunteers (Olanoff et al, 1984;Walle et al, 1983;Albani et al, 1984). We were not, however, able to demonstrate any influence of age itself upon the binding of either of the propranolol enantiomers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although the differences were small, the data nonetheless are consistent with previous reports that have demonstrated the stereoselective binding of (-)-propranolol in young, healthy volunteers (Olanoff et al, 1984;Walle et al, 1983;Albani et al, 1984). We were not, however, able to demonstrate any influence of age itself upon the binding of either of the propranolol enantiomers.…”
Section: Discussionsupporting
confidence: 80%
“…Studies dealing with the stereoselective binding of propranolol in man are, at present, limited and mainly involve young subjects (Olanoff et al, 1984;Walle et al, 1983;Albani et al, 1984). Many elderly individuals receive propranolol and there is evidence to suggest altered pharmacokinetics and/or pharmacological effect in this population (Vestal et al, 1979a;Paxton & Briant, 1984;Schumucker, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, progress in the development of analytical methods for the efficient resolution of enantiomers has facilitated studies of the differences in the pharmacological properties of the enantiomers of many chiral agents, and it has been shown that such differences can originate from stereoselectivity in their absorption (22), distribution (1,26), receptor binding (23), metabolism (17,18) and/or excretion (10). Among the quinolone antibacterial agents there are many drugs, such as lomefloxacin, sparfloxacin, and OFLX, which possess an asymmetric carbon in their chemical structures.…”
Section: Discussionmentioning
confidence: 99%
“…The two different genes which code for AAG in humans, code for two proteins differing by 22 amino acid substitutions [5]. Genetic characterization of the AAG variants [6,13] [22,23].…”
Section: Discussionmentioning
confidence: 99%